Implementation of Positive Discipline Through Strengthening Learning Communities Assisted by Artificial Intelligence in MIM 2 Babakan - Windiatmoko, Doni Uji; Fanani, Istiqlal Yul; Faujie, Indy Alfin; Nugraha, Gandhi Putra (IKIP PGRI Bojonegoro, 2025)
Positive discipline characterizes an educational institution that has habits, character, and regulations that reflect an effective spirit and commitment. With the help of ChatGPT, strengthening learning communities and coaching practices in madrasas become facilities to support the implementation of positive discipline. The research method uses a mixed methods approach with questionnaires (pretest-posttest), direct interviews, and non-participatory observations of madrasah principals and teachers. The results of the study indicate that strengthening learning communities and coaching practices assisted by ChatGPT can strengthen or support the implementation of positive discipline in madrasas. The questionnaire also found surprising results from the pretest and posttest which indicated an increase in knowledge and good practices in implementing positive discipline (average score results 41,6 –> 69,3) . The conclusion of the study is that with the help of artificial intelligence, it can help principals and teachers to create a better classroom atmosphere and student attention in implementing positive discipline. Strengthening learning communities and coaching practices also have a positive impact on the implementation of positive discipline in madrasah.